Hadist-Hadist Tentang Pedoman Hidup Sekaligus Dasar Penyelenggaraan Pendidikan dan Potensi-Potensi/ Keunggulan Manusia Yang Perlu di Kembangkan Lewat Pendidikan - Anisa Putri Ardana; Fitri Rahmadani; Mardina Wati; Selvina Zulpa; Wismanto Wismanto (STIKes Ibnu Sina Ajibarang, 2024)
The quality of a nation is largely determined by educational factors. Education is essentially a conscious effort to prepare students through guidance, teaching or training activities for their roles in the future. Or in other words, education is a conscious effort to develop the potential of students' human resources by encouraging and facilitating their learning activities, so that in developing their duties teachers are required to be able to educate, teach and train so that mastery of concepts is more ingrained. This research aims to reveal hadiths related to life guidelines which are the basis for the implementation of education as well as exploring the potential that exists and needs to be developed in humans. This research uses qualitative research with a library research approach. The results of this research show that there are several potentials that need to be developed, including; Intellectual Mental Potential (Intellectual Quotient). Social Emotional Potential (Emotional Quotient). Spiritual Mental Potential (Spiritual Quotient). Fighting Potential (Adversity Quetient) and Physical Potential (Psychomotor).